2020
DOI: 10.1007/s10596-020-10007-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase-field modelling of crack propagation in geological materials and porous media with Drucker-Prager plasticity

Abstract: A multiphase-field approach for elasto-plastic and anisotropic brittle crack propagation in geological systems consisting of different regions of brittle and ductile materials is presented and employed to computationally study crack propagation. Plastic deformation in elasto-plastic materials such as frictional, granular or porous materials is modelled with the pressure-sensitive Drucker-Prager plasticity model. This plasticity model is combined with a multiphase-field model fulfilling the mechanical jump cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…For instance, a double phase-field model for tensile, shear, and mixed-mode fracture with plasticity was proposed in You et al [86], while other studies [3,87] focus on modeling the brittle-to-ductile transition phenomenon. Phase-field models coupled to frictional plasticity have been further considered in the finite strain setting [3,88], as well as in the context of multiphase materials [89] and fluiddriven fracture [90,91]. Moreover, building upon the phase-field modeling of frictional interfaces [77], Bryant and Sun [92] proposed a model that embeds rate-, size-, and temperature-dependent friction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a double phase-field model for tensile, shear, and mixed-mode fracture with plasticity was proposed in You et al [86], while other studies [3,87] focus on modeling the brittle-to-ductile transition phenomenon. Phase-field models coupled to frictional plasticity have been further considered in the finite strain setting [3,88], as well as in the context of multiphase materials [89] and fluiddriven fracture [90,91]. Moreover, building upon the phase-field modeling of frictional interfaces [77], Bryant and Sun [92] proposed a model that embeds rate-, size-, and temperature-dependent friction.…”
Section: Introductionmentioning
confidence: 99%
“…According to the abovementioned results, which include Formulas ( 16), ( 29), (32), (34) and (37), a series of analytical solutions comprises the modified Fenner formula based on joint strength. In this section, the difference between the modified Fenner formula based on joint strength and the modified Fenner formula based on M-C strength [7] for the unlined loess tunnel will be analysed and discussed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Drucker-Prager (D-P) strength criterion was put forward to overcome the corner defect in M-C strength in π plane; it is widely used in numerical analysis of geotechnical engineering. Multiphase-field modelling of crack propagation in geological materials and porous media was analysed based on D-P strength criterion [7]. The king of theoretical solutions in tunnel-excavation processes was deduced through the cavity-expansion theory based on the D-P strength criterion [8].…”
Section: Introductionmentioning
confidence: 99%
“…The second approach is the more general multiphase-field framework [8,9,14] based on Allen-Cahn equations for the evolution of non-conserved order parameters in combination with the evolution of diffusional potential based on the grand-chemical potential [29,30]. This framework has been sucessfully combined with elastic driving forces based on jump conditions [31,32] to model martensitic transformations [12], crack propagation [33][34][35] and the evolution of electric field to study electromigration [36]. It has further been shown that grain boundary diffusion [37] as well as the instability leading to phase separation in the miscibility gap [6] can be effectively modelled.…”
Section: Introductionmentioning
confidence: 99%